2020
DOI: 10.1037/cdp0000296
|View full text |Cite
|
Sign up to set email alerts
|

The impact of social support on adolescent coping in the context of urban poverty.

Abstract: This study used a mixed method, prospective, multi-informant design to (a) identify coping strategies used by youth residing in urban poverty and (b) test whether these coping strategies buffer the effects of stress exposure when adult support is present and when absent. Method: There were 286 youth ages 10 to 16 (mean age at Time 1 ϭ 13; 65% female; 34% male; 1% not identified; 46% African American; 25% Latino; 11% European American; 8% Asian American, 4% Mixed/Biracial, 6% Other) and their parents who partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 101 publications
1
12
0
Order By: Relevance
“…shows that the Direct Influence Graph means that perception-motivation has a partial relationship with digital transactions, while the social impact of management risk has a multivariate relationship with the variables of quality of life-service, social-cultural network of consumers, and customer satisfaction. Correlated among perception-motivation with digital transaction in line of found of [19]- [21]. Fig.…”
Section: The Mapping Of Key Variablesmentioning
confidence: 71%
“…shows that the Direct Influence Graph means that perception-motivation has a partial relationship with digital transactions, while the social impact of management risk has a multivariate relationship with the variables of quality of life-service, social-cultural network of consumers, and customer satisfaction. Correlated among perception-motivation with digital transaction in line of found of [19]- [21]. Fig.…”
Section: The Mapping Of Key Variablesmentioning
confidence: 71%
“…In many regions of the world problematic social and racial relationships, poverty, low educational level, and few job possibilities are concerns which might contribute to participation in risky behavior (unsafe sexual activity, risky driving, alcohol or drug intoxication, etc) [9,67] . Also, adolescents who reside in low-income urban neighborhoods, with systemic discrimination and economic deprivation, are exposed to a range of severe and chronic stressors beyond those that are typical for the general population [68,69] . Exposure to violence (both as a victim and as a witness) and to other stressors associated with urban poverty contribute to heightened rates of psychological problems among lowincome urban youth [69] .…”
Section: Social Contextmentioning
confidence: 99%
“…Also, adolescents who reside in low-income urban neighborhoods, with systemic discrimination and economic deprivation, are exposed to a range of severe and chronic stressors beyond those that are typical for the general population [68,69] . Exposure to violence (both as a victim and as a witness) and to other stressors associated with urban poverty contribute to heightened rates of psychological problems among lowincome urban youth [69] .…”
Section: Social Contextmentioning
confidence: 99%
“…24 Stacey et al 25 examined the relationship between self-care and social support and concluded that these two variables have a significant relationship with each other. Reife et al 26 inspected the impact of social support on coping techniques and showed that by increasing social support, individuals use more effective coping methods and experience a better mental health status. Stapley et al 27 concluded that self-care behaviors and social support play an important role in people's health and their ability to stress.…”
Section: Introductionmentioning
confidence: 99%